2001
DOI: 10.1590/s0100-06832001000300024
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e nodulação de Acacia mangium, Enterolobium contortisiliquum e Sesbania virgata em solo contaminado com metais pesados

Abstract: SUMMARY: GROWTH AND NODULATION OF : 0, 15, 30, 45 and 60% (v/v) with Zn, Cd, Pb and Cu (18.600, 135, extracted by aqua regia, respectively), diluted in a low fertility Oxisol. The species were inoculated with recommended strains (S) (Zn = 750; Cd = 22.1; extracted by DTPA) the specific activity of nitrogenase was stimulated, increasing 5 and 10 times in relation to the soil without contamination for the sesbânia-BR 5401 and tamboril-BR 4406 symbiosis, respectively. Rhizobia's "in vitro" tolerance to heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…(27), the cultivation of three woody plant species ( Acacia mangium , Enterolobium contortisiliquum and Sesbania virgata ) in heavy metal contaminated soil had a negative effect on the growth, dry weight of the aerial parts, height, and stem diameter of these plants. These authors observed a phytotoxic effect of the metals on the three species for soils with 15% contamination.…”
Section: Resultsmentioning
confidence: 99%
“…(27), the cultivation of three woody plant species ( Acacia mangium , Enterolobium contortisiliquum and Sesbania virgata ) in heavy metal contaminated soil had a negative effect on the growth, dry weight of the aerial parts, height, and stem diameter of these plants. These authors observed a phytotoxic effect of the metals on the three species for soils with 15% contamination.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that plants using Nitrogen from symbiosis with rhizobia are less tolerant to various stress than when they utilize combined Nitrogen (Trannin et al 2001b). This was the case of all A. amazonense strains and isolates, and A. brasilense strain 1R, however the other isolates/strains behaved in an opposite way.…”
Section: Discussionmentioning
confidence: 90%
“…According to the same author, its wood is appropriate for manufacturing whole-trunk boats and canoes, toys, plywood and furniture frames. Additionally, it presents some tolerance to heavy metals, showing promise for research aimed at the revegetation of soils that contain excessive levels of these elements (Andrade, 2005;Trannin et al, 2001). Further, it also presents rapid initial growth (Araújo & Sobrinho, 2011).…”
Section: Introductionmentioning
confidence: 99%